2016
DOI: 10.1038/srep22588
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensionally Ordered Macroporous Structure Enabled Nanothermite Membrane of Mn2O3/Al

Abstract: Mn2O3 has been selected to realize nanothermite membrane for the first time in the literature. Mn2O3/Al nanothermite has been synthesized by magnetron sputtering a layer of Al film onto three-dimensionally ordered macroporous (3DOM) Mn2O3 skeleton. The energy release is significantly enhanced owing to the unusual 3DOM structure, which ensures Al and Mn2O3 to integrate compactly in nanoscale and greatly increase effective contact area. The morphology and DSC curve of the nanothermite membrane have been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The diffraction peaks represented by the (#) located at angle 23.01, 30.68, 36.83, and 53.58 degrees correspond to the Mn2O3 planes of the (211), (222), (400), and (440) orientations (JSPDS No. 41-1442) [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peaks represented by the (#) located at angle 23.01, 30.68, 36.83, and 53.58 degrees correspond to the Mn2O3 planes of the (211), (222), (400), and (440) orientations (JSPDS No. 41-1442) [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…After melting of Al film, the melted Al reacted with a MnO 2 beneath the MnO 2 nano-films at an onset temperature of about 830 °C. This exothermal reaction occurred by a liquid-solid diffusion mechanism [32, 33]. The heat releases of MnO 2 /Al-132 nm and MnO 2 /Al-400 nm at a heating rate of 20 °C min −1 were 1241.0 and 1659.0 J/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that magnetron sputtering offers controllable coverage 10 density of Al through adjusting deposition time [34]. Fig.…”
Section: Morphology Characterizationsmentioning
confidence: 99%